Pengaruh Kompetensi, Pengalaman Kerja Independensi Akuntabilitas Integritas Dan Obyektivitas Terhadap Kualitas Audit - Mahyasari, Khanipa; , Drs. Muhammad Abdul Aris, M.Si (2016)
This research is intended to analyze the effect of the competence, work experience, independence, accountability, integrity and obyectivity of the audit quality in the Government Inspectorate se-Eks Karesidenan Surakarta. The population in this research are all auditors working in the Inspectorate se-Eks Karesidenan Surakarta. The sampling method was done by using purposive sampling according to criteria that have been determined. The number of samples collected as many as 83 auditors. This research uses multiple linear regression analysis mode. The results of this research showed that the variables of competence, work experience, independence, accountability, integrity and objectivity have significantly effect on audit quality. Keywords: competence, work experience, independence, accountability, integrity, obyectivity, and audit quality